Features of the formation of speech competencies of students in Uzbek schools - Botirov A.A, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The main task of teaching the Russian language to students in Uzbek schools is to equip students with speech competencies, i.e. learning - reading, writing, speech perception, speaking, the ability to participate in a conversation, make observations, draw conclusions, express them in verbal form. Teaching Russian literacy in the Uzbek school has its own specific features and difficulties. First of all, it is necessary to take into account the fact that by this time children already have the basic skills of reading and writing in their native language. They have already acquired the initial skills of decomposing words into syllables and sounds and merging sounds (syllables), they know how words are formed from letters. When teaching literacy in their native language, children have mastered the "mechanics" of reading in the sense of reproducing sound combinations by graphic icons - letters and they perceive Russian sounds through the prism of their native language. But the fact is that in the overwhelming majority of Russian syllables and words the sounds themselves will be qualitatively different from the sounds of native speech familiar to the student